Exploration of Ethnomatematics in the Samin Tribe and Its Relationship with Mathematical Concepts - Ahadi, Faiq Al; Zaenuri, Zaenuri; Cahyono, Adi Nur (Unnes Journal of Mathematics Education Research, 2021)
This study aims to determine the effectiveness of the Contextual learning model nuanced ethnomatematics of Samin Tribe. The subjects of this research were grade VIII of SMP N 4 Ngawen. This type of research was mixed methods. The research design was One Group Pretest Posttest Design. Data collection techniques used tests, observations, documentation, and interviews. Based on the research results, ethnomatematics forms in the Samin tribe contained in traditional ceremonies in the form of the implementation of traditional ceremonies, did not have art, buildings in the form of Bekuk Lulang’s house, livelihood in the form of farmers (Samin tribal calendar, taun, tuwan/wulan, dino, wengi , suro, mangso udan, mangso garing) and breeders (cows and goats), woven in the form of Klasa Pandan, woven in the form of a headband (Blangkon), traditional games in the form of Dakon, delikan and jamuran, traditional food in the form of Tumpeng and Ketupat. The relationship between ethnomatematic forms of the Samin tribe with mathematical concepts namely number patterns, integer operations, geometry and measurements. The implementation of mathematics learning in SMP with the contextual ethnomatematics nuanced by the Samin tribe was effective with the achievement of KKM.